Larvacidal Effect of Imperata Cylindrical Root Decoction against Culex sp. Larvae - Resi, Afini Tiara; Dhianawaty, Diah; Syarifah, Neneng (Althea Medical Journal, 2014)
Background: Filariasis is one of the neglected tropical diseases. About 337 of 401 districts in Indonesia are endemic areas for filariasis, especially in Sumatera,  Kalimantan, and Papua. Culex sp. is one of the lymphatic filariasis vectors which can be controlled by insecticide, including larvacide. This study was conducted to determine the larvacidal effect of Imperata cylindrical root decoction against Culex sp. larvae.Methods: This study was conducted at the Laboratory of Parasitology, Faculty of Medicine, Universitas Padjadjaran during the period of September to November 2012. The study object was Culex sp. larvae III/IV instars. The design of this study was experimental laboratory using true experimental approach. The larvae were divided into three groups: negative control (distilled water), reference (Abate®), and decoction. The number of larvae in each group was 25 larvae, and the effects were evaluated by the total number of dead larvae in 48 hours under observation. The data were then analyzed by Mann-Whitney test and Probit test.Results: The result of the Mann-Whitney test to compare Imperata cylindrica root decoction treatment to distilled water as control  was significant (p<0.05). However, Abate® gave a better result. The Probit test resultwas LC50:  63% and LC90: 489%.Conclusions: Imperata cylindrical root decoction has a larvacidal effect against Culex sp. larvae.Keywords: Culex sp., Filariasis, Imperata cylindrica (L.) Beauv., Larvacidal, LC50  Pengaruh Larvasida Rebusan akar alang-alang (Imperata Cylindrical) terhadap Larva Nyamuk (Culex sp.) AbstrakLatar Belakang: Filariasis merupakan salah satu penyakit tropis yang terabaikan. Sekitar 337 dari 401 kabupaten di Indonesia adalah daerah endemik untuk filariasis terutama di Sumatera, Kalimantan, dan Papua.  Nyamuk (Culex Sp.) adalah salah satu vektor filariasis limfatik yang dapat dikendalikan oleh insektisida, termasuk larvasida. Penelitian ini dilakukan untuk mengetahui pengaruh larvasida dari rebusan  akar alang-alang terhadap larva nyamuk (Culex sp.)Metode: Penelitian ini dilakukan di Laboratorium Parasitologi, Fakultas Kedokteran, Universitas Padjadjaran selama periode September-November 2012. Objek penelitian adalah larva nyamuk (Culex sp.) instar III / IV.. Desain penelitian ini adalah eksperimental laboratoris dengan menggunakan pendekatan eksperimental yang benar. Larva dibagi menjadi tiga kelompok: kontrol negatif (air suling), referensi (Abate®), dan rebusan. Jumlah larva dalam setiap kelompok adalah 25 larva, dan efek dievaluasi dengan jumlah total larva mati dalam 48 jam di bawah pengawasan. Data kemudian dianalisis dengan uji Mann-Whitney dan uji Probit. Hasil: Hasil uji Mann-Whitney untuk membandingkan pemberian rebusan akar alang-alang (Imperata cylindrica) terhadap air suling sebagai kontrol adalah signifikan (p <0,05). Namun, Abate® memberikan hasil yang lebih baik. Hasil tes Probit adalah LC50: 63% dan LC90: 489%.Simpulan: Rebusan akar alang-alang (Imperata cylindrical) memiliki efek larvsidal terhadap larva nyamuk (Culex sp.) Kata kunci: Nyamuk (Culex sp.), Filariasis, Alang-alang (Imperata cylindrica (L.) Beauv), Larvasida, LC50 DOI: 10.15850/amj.v1n2.349